Chilling-injury and disturbance of ion homeostasis in the coxal muscle of the tropical cockroach (Nauphoeta cinerea) - Kostál, V; Yanagimoto, M; Bastl, J (Comparative biochemistry and physiology. Part B, Biochemistry & molecular biology, 2006)
Adults of warm- and cold-acclimated tropical cockroaches, Nauphoeta cinerea were exposed to low temperatures of 0 or 5 degrees C for various time intervals (hours to days). Development of chilling-injury (defects in crawling and uncoordinated movements) and mortality during the exposure were assessed and correlated with the changes in concentrations of metal ions (Na(+), K(+) and Mg(2+)) in the haemolymph and coxal muscle tissue. Warm-acclimated insects entered chill-coma at both low temperatures. In their haemolymph, the [Na(+)] and [Mg(2+)] linearly decreased and [K(+)] increased with the increasing time of exposure. The rate of concentration changes was higher at 0 than at 5 degrees C. The concentration changes resulted in gradually dissipating equilibrium potentials across the muscle cell membranes. For instance, E(K) decreased from -49.8 to -20.7 mV during 7 days at 5 degrees C. Such a disturbance of ion homeostasis was paralleled by the gradual development of chilling-injury and mortality. Most of the cockroaches showed chilling-injury when the molar ratio of [Na(+)]/[K(+)] in their haemolymph decreased from an initial of 4.4 to 2.1-2.5. In contrast, the cold-acclimated cockroaches did not enter chill-coma. They maintained constant concentrations of ions in their haemolymph, constant equilibrium potentials across muscle cell membranes and the development of chilling-injury was significantly suppressed at 5 degrees C for 7 days.
Keywords: buněčná membrána; Cockroaches; aklimatizace; nízká teplota; kosterní svaly; Animals; Cell Membrane; Membrane Potentials; Acclimatization; švábi; homeostáza; membránové potenciály; kovy; Metals; zvířata; Homeostasis; Muscle, Skeletal; Cold Temperature